Uncharted : Lewis and Clark in Arcane America - Anderson, Kevin J., 1962-; Hoyt, Sarah A.; Flint, Eric; Hunt, Walter C.; Kollin, Eytan; Wacks, Peter J., 1976- (Baen, 2018)
"New Alternate History Fantasy series created by New York Times best-selling author Kevin J. Anderson and Sarah A. Hoyt. Arcane America. A new world. New magic. New history. After Halley's Comet was destroyed in a magical battle in 1759, the backlash separated the entire New World from the Old in an event known as The Sundering. Now isolated from the rest of the globe, America has become a very different place, where magic works and history has been changed forever. It is 1803--a new 1803. Young Meriwether Lewis, footloose and intrigued, goes to hear a lecture in St. Louis by the venerated old wizard Benjamin Franklin. Franklin's talk is disrupted by the attack of a winged fire-breathing beast, much like legends from Lewis's own Welsh heritage. In the aftermath, Franklin tells the young man that he knows of a great, growing evil that lurks in the uncharted Arcane Territories west of the Mississippi. Using his own vast fortune, Franklin commissions Lewis and his own talented partner William Clark to embark on a remarkable voyage of exploration, to meet and document the indigenous tribes, to find a route all the way to the Pacific Ocean--and perhaps beyond the magical veil to Europe again--and to stop the growing evil that is filling the American West. For while the Sundering separated the rest of the world and granted the original colonists unexpected magical gifts, sorcery inspired by native legends has also been ignited. And the Arcane Territories may hold unparalleled dangers for the expedition, both natural and magical. Accompanied by the brilliant shape-shifting sorceress Sacajawea, Lewis and Clark set off on an unparalleled adventure across a landscape that no European has ever seen. About Kevin J. Anderson: "Anderson delivers action, engaging characters and credible fantastic worlds in spades. not to be missed."--Publishers Weekly "Wickedly funny, deviously twisted and enormously satisfying."--Jonathan Maberry "Anderson has become the literary equivalent of Quentin Tarantino in the fantasy adventure genre."--The Daily Rotation "Prepare to be entertained." --Charlaine Harris "Delivers solid action and will certainly satisfy."--Booklist on The Winds of Dune About Sarah A. Hoyt: "[Three Musketeers creator] Alexandre Dumas would give [Sarah A. Hoyt] a thumbs up." --Steve Forbes "[F]anciful and charming." --Library Journal "First-rate space opera with a moral lesson. You won't be disappointed."--Glenn Reynolds, Instapundit.com "[A] tour de force: logical, built from assumptions with no contradictions. gripping." --Jerry Pournelle "Exceptional, wonderful, and enormously entertaining." --Booklist"--